Experiences of Patient-Centredness With Specialized Community-Based Care: A Systematic Review and Qualitative Meta-Synthesis - Winsor, S (Health Quality Ontario, 2013)
BACKGROUND: Specialized community-based care (SCBC) endeavours to help patients manage chronic diseases by formalizing the link between primary care providers and other community providers with specialized training. Many types of health care providers and community-based programs are employed in SCBC. Patient-centred care focuses on patients’ psychosocial experience of health and illness to ensure that patients’ care plans are modelled on their individual values, preferences, spirituality, and expressed needs. OBJECTIVES: To synthesize qualitative research on patient and provider experiences of SCBC interventions and health care delivery models, using the core principles of patient-centredness. DATA SOURCES: This report synthesizes 29 primary qualitative studies on the topic of SCBC interventions for patients with chronic conditions. Included studies were published between 2002 and 2012, and followed adult patients in North America, Europe, Australia, and New Zealand. REVIEW METHODS: Qualitative meta-synthesis was used to integrate findings across primary research studies. RESULTS: Three core themes emerged from the analysis: patients’ health beliefs affect their participation in SCBC interventions; patients’ experiences with community-based care differ from their experiences with hospital-based care; patients and providers value the role of nurses differently in community-based chronic disease care. LIMITATIONS: Qualitative research findings are not intended to generalize directly to populations, although meta-synthesis across several qualitative studies builds an increasingly robust understanding that is more likely to be transferable. The diversity of interventions that fall under SCBC and the cross-interventional focus of many of the studies mean that findings might not be generalizable to all forms of SCBC or its specific components. CONCLUSIONS: Patients with chronic diseases who participated in SCBC interventions reported greater satisfaction when SCBC helped them better understand their diagnosis, facilitated increased socialization, provided them with a role in managing their own care, and assisted them in overcoming psychological and social barriers. PLAIN LANGUAGE SUMMARY: More and more, to reduce bed shortages in hospitals, health care systems are providing programs called specialized community-based care (SCBC) to patients with chronic diseases. These SCBC programs allow patients with chronic diseases to be managed in the community by linking their family physicians with other community-based health care providers who have specialized training. This report looks at the experiences of patients and health care providers who take part in SCBC programs, focusing on psychological and social factors. This kind of lens is called patient-centred. Three themes came up in our analysis: patients’ health beliefs affect how they take part in SCBC interventions; patients’ experiences with care in the community differ from their experiences with care in the hospital; patients and providers value the role of nurses differently. The results of this analysis could help those who provide SCBC programs to better meet patients’ needs.